PRINCIPAL COMPONENT ANALYSIS OF VOCATIONAL TEACHER COMPETENCY IN EAST SERAM REGENCY - Rahmaddhiyanto, Arif; Wenno, Izaak Hendrik; Rahabav, Patrisius (LPPM Univ. Ibn Khaldun Bogor, 2026)
This research aims to identify the dominant factors that shape the competence of vocational teachers in the region. The variables studied include: (X1) Understanding of educational insight or foundations; (X2) Understanding of students; (X3) Curriculum or syllabus development; (X4) Instructional design; (X5) Mastery of learning technology; (X6) Implementation of educational and dialogic learning; (X7) Evaluation of learning outcomes; (X8) Development of students to actualize their various potentials; (X9) Learning management skills; (X10) Use of multimedia in learning; (X11) Application of didactic-methodological principles; (X12) Ability to evaluate and develop effective tests; (X13) Acting in accordance with religious, legal, social, and Indonesian national cultural norms; (X14) Displaying an honest and noble character; (X15) Behaving maturely and authoritatively; (X16) Demonstrating a strong work ethic, responsibility, pride in being a teacher, and self-confidence; (X17) Ability to uphold the teacher's code of ethics; (X18) Non-discriminatory attitude in learning management; (X19) Interpersonal communication skills; (X20) Adapting to socio-cultural diversity; (X21) Multi-dimensional professional communication skills. The collected data were then analyzed using Principal Component Analysis (PCA) to reveal the variables that influence the competence of vocational teachers in East Seram Regency. From the 21 variables, 5 variables with an MSA value below 0.5 were eliminated. After the extraction process, 5 dominant factors were obtained: Skills, Integrity, Innovation, Knowledge, and Attitude.